RNA binding proteins (RBPs) on genetic stability and diseases - Abdullahi Tunde Aborode; Ohilebo Abdulateef Abass; Shaibu Nasiru; Mary Ugunnushe Eigbobo; Sumana Nefishatu; Abdullahi Idowu; Zainab Tiamiyu; Aeshah A. Awaji; Nike Idowu; Babawale Roqeeb Busayo; Qasim Mehmood; Isreal Ayobami Onifade; et al. (Global Medical Genetics)
RNA-binding proteins (RBPs) are integral components of cellular machinery, playing crucial roles in the regulation of gene expression and maintaining genetic stability. Their interactions with RNA molecules govern critical processes such as mRNA splicing, stability, localization, and translation, which are essential for proper cellular function. These proteins interact with RNA molecules and other proteins to form ribonucleoprotein complexes (RNPs), hence controlling the fate of target RNAs. The interaction occurs via RNA recognition motif, the zinc finger domain, the KH domain and the double stranded RNA binding motif (all known as RNA-binding domains (RBDs). These domains are found within the coding sequences (intron and exon domains), 5’ untranslated regions (5’UTR) and 3’ untranslated regions (3’UTR). Dysregulation of RBPs can lead to genomic instability, contributing to various pathologies, including cancer neurodegenerative diseases, and metabolic disorders. This study comprehensively explores the multifaceted roles of RBPs in genetic stability, highlighting their involvement in maintaining genomic integrity through modulation of RNA processing and their implications in cellular signalling pathways. Furthermore, it discusses how aberrant RBP function can precipitate genetic instability and disease progression, emphasizing the therapeutic potential of targeting RBPs in restoring cellular homeostasis. Through an analysis of current literature, this study aims to delineate the critical role of RBPs in ensuring genetic stability and their promise as targets for innovative therapeutic strategies.